The Moderating Role of Entrepreneurial Competence in the Developmentof a Sharia-Based Micro, Small, and Medium Enterprise (MSME) Performance Model - hardianti yusuf; Fasiha; Umar; Muh. Ginanjar; Arkas Maulana; Nurul Khairiyah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the factors influencing the performance of sharia-based micro, small, and medium enterprises (MSMEs) in Luwu Raya, Sulawesi Selatan, Indonesia, with a specific focus on the moderating role of entrepreneurial competence. The research is motivated by the limited number of studies that combine Islamic financial aspects with entrepreneurial capacity in improving MSME performance. A quantitative approach was employed, and the sample was determined using the Lemeshow formula, resulting in 96 respondents. Data were collected through a structured questionnaire and analyzed using Structural Equation Modeling with the Partial Least Squares (PLS-SEM) method, utilizing the SmartPLS software. The independent variables in this study include Islamic financial inclusion, Islamic financial literacy, and Islamic microfinance institutions. The dependent variable is MSME performance, while entrepreneurial competence serves as the moderating variable. The findings show that all independent variables have a positive and significant effect on MSME performance. Additionally, entrepreneurial competence not only has a direct impact on performance but also strengthens the relationship between Islamic financial inclusion and the role of Islamic microfinance institutions in improving performance. However, no moderating effect was found in the relationship between financial literacy and performance. These results highlight that access to Islamic financial services and institutional support alone is not sufficient; strong entrepreneurial skills are also needed to ensure sustainable growth and competitiveness of MSMEs operating within the framework of Islamic economic principles.